O-BN01 The para-oesophageal hernia symptom tool (post): A modified delphi consensus study. (16th December 2021) - Puri, Aiysha; Patel, Nikhil; Sounderajah, Viknesh; Ferri, Lorenzo; Griffiths, Ewen; Low, Donald; Maynard, Nick; Mueller, Carmen; Pera, Manuel; van Berge Henegouwen, Mark; Watson, David; Zaninotto, Giovanni; et al.
Abstract: Background: Patients with a para-oesophageal hernia (POH) report a complex range of symptoms and quality of life (QOL) issues. Clinicians often utilise existing health related quality of life tools to (1) identify patients who are eligible for surgical management and (2) to evaluate the benefit of surgical intervention. However, the most commonly used tools for this purpose are not disease specific. As such, crucial POH specific symptoms which impact QOL may not be captured. In order to address this issue, a modified Delphi consensus study was undertaken to establish a HRQOL instrument specific to POH. Methods: A two-round modified Delphi consensus study was conducted with a group of international experts. Participants were identified through (1) their authorship in landmark POH studies and (2) the professional networks of the study investigators. Prior to the Delphi process, a scoping survey was undertaken in order to generate a list of candidate items. Participants were asked to rate the items' importance in assessing patients with POH using a 5-point Likert scale. The a priori threshold for inclusion was 80% for scores of 4 or 5. If consensus was not achieved, the item was carried through to the next round. Results: The candidate list of items consisted of 64 symptoms, refined to 20 for inclusion within the first modified Delphi round. Four symptoms; 'difficulty getting solid foods down', 'chest pain after meals', 'difficulty getting liquids down' and 'shortness of breath only after meals', reached consensus threshold of 80% in the first round and one additional symptom, 'early feeling of fullness after eating', reached consensus in the second. A total of 26 participants took part in the first and 24 in the second round. These five symptoms have been identified to form the initial version of the Para-Oesophageal Hernia Symptom Tool (POST). Conclusions: POST is the first tool that aims to capture POH-specific symptoms that impact upon HRQOL. Prior to clinical use, this tool will be presented in international patient workshops to assess its construct validity. Following this, we aim to assess the content validity of the tool through a longitudinal study in a cohort of patients with POH who are undergoing repair. We hope that this tool will serve as a decision support tool for clinicians who are evaluating the risk-benefit of surgical intervention in this cohort of patients.